The Effectiveness of Using E-Modules as Digital Learning Media in the Learning of Islamic Education - Qurrotu’ain, Salsabila; Shohib, Muhammad Wildan; Nubail, Ahmad (Universitas Muhammadiyah Surakarta, 2024)
The advancement of science and technology, which is increasingly sophisticated today, has caused various kinds of changes in human life, including changes in the learning system. This study aims to determine the extent of the effectiveness of the use of e-modules in learning Islamic religious education. This research method is included in the type of qualitative field study research with a phenomenological approach to reveal facts in order to obtain data by making observations, documentation, and interviews with Islamic religious education teachers and the Science Technology team at Muhammadiyah Al Kautsar High School. Valid data analysis techniques in this study were carried out through observation and interviews with Islamic religious education teachers. In addition, researchers also conducted an official web analysis at Muhammadiyah Al Kautsar High School and then carried out data processing. The document analysis was put together into conclusions that were the results of the study. The results of this study show that the impact of using e-modules is effective in Islamic religious education. This study focuses on the perspective of students on the use of e-modules in Islamic religious education learning as well as the effectiveness of using e-modules in Islamic religious education learning.